Revivalisme Islam dan Implikasinya Terhadap Perempuan di Indonesia - Dzuhayatin, Siti Ruhaini (Musawa Jurnal Studi Gender dan Islam, 2010)
The revving up of narrow, 'Syari'ah' based revivalist movements is chaining down the movement of women as a whole. Thanks to a concept of Syari'ah that is decidedly misogynic in putting forth rules and legislations; containing quite a bit of hatred against women, rooted in a religious view that is negatively sexual, and aimed at the female body. This has lead to simplification, reduction and generally destructive confusion manifested in numerous acts of Jilbabisasi and one-sided clothing regulations. Trampling over diversity, and taking down long...standing traditional clothing that has created no previous moral problems, some of which has become rooted in the identities of a culture, as collateral damage.